Comparative study on engineering and functional properties of black gram - ANUSHKA MITRA; SABAH SHEHABUDHEEN; CHANDRANI DUTTA; NIVETHA KATHIRAVAN; RAHUL ANANTH (International Journal of Pharma and Bio Sciences, 2019)
Black gram (Vigna mungo L.) is one of the oldest known pulses to man, it is said to have originated in the Indian subcontinent and slowly spread to different parts of the world including parts of the Caribbean, Fiji, Mauritius and Africa. It has been extensively cultivated since ancient times and is popular in most households till date due to its high nutritive value and unique flavour. It is imperative for every food engineer to be well informed about the physical properties of food, in order to help in planning various operations like design, modeling and optimization of processes. The in-depth study of such engineering properties is a fairly new discipline, it holds high regard in the industry due to its direct correlation to product quality. This study deals with the intricate study of physical and mechanical properties of Black gram and here selected physical properties of Black gram (Vigna mungo L.) were studied extensively in 5 physical forms, namely (i) whole black gram, (ii) peeled black gram, (iii) sprouted black gram, (iv) split black gram, (v) split and peeled black gram. Dimensional analysis for the sample was performed and this included evaluating the arithmetic and geometric mean. The size of the grain, its sphericity, grain volume and thousand grain mass (test weight) were also evaluated. Moisture content was uniformly obtained to be 8.11±0.02 %, except in the case of sprouted black gram where it was 14.24±0.03 %. The angle of repose increased linearly from 25.31°±0.02 to 37.53°±0.02. A comprehensive study of many such properties was thus conducted.